A weight‐related growth mindset increases negative attitudes toward obese people. Issue 9 (21st August 2018) - Hooper, Nic; Crumpton, Alison; Robinson, Michael D.; Meier, Brian P.
Abstract: In implicit personality theory, people with entity views or a fixed mindset perceive characteristics (e.g., intelligence) as uncontrollable, whereas people with incremental views or a growth mindset perceive characteristics as controllable. In addition to other benefits, the literature sometimes suggests that having a growth mindset will protect against prejudice, which the current two studies examine in terms of negative attitudes toward obese people. Participants (total N  = 501) were randomly assigned to complete a questionnaire assessing attitudes toward an obese or nonobese person and a self‐theory questionnaire also assessed ideas about body weight. People with a growth mindset, and not fixed mindset, were more likely to have negative attitudes toward obese individuals, pointing to a potential downside of growth mindset in the obesity domain.